Development of School Geographical Education in Ukraine in The First Half of the XX Century (1905–1917) - Shorobura, Inna (Pedagogical Discourse, 2017)
Formation of domestic geographic education at the beginning of the XX century testifies that its improvement in this period was directly conditioned by the socio-economic and political factors of development of the society, which gave rise to changes in the development of geographical education. The first decades of the XX century are characterized by increased attention of the society to the study of geography. Geography is introduced into the programs of educational institutions of almost all types, although in different types of schools it occupied an ambiguous place in curricula and was taught according to different programs. The teachers also created their own programs at their schools. In some of them the level of teaching geography and natural science has not always been appropriate, because the work in the classroom was reduced to memorizing of geographical names. However, one could see intensification of methodological thought, especially as for the development of methods of teaching the initial course of physical geography. One of the most common forms of extracurricular activity of pupils becomes the conduct of local lore excursions, which facilitated the widespread use of the material of observation and the formation of practical abilities of pupils when teaching natural courses. Scholastic teaching methods are blamed; the attention is drawn to the necessity of establishing causal connection between the disparate geographical phenomena. Drawing and coloring maps became the obligatory part of the lesson. The first textbooks of the new type by P. Brounov, A. Svyrydov, E. Leshaft, H. Ivanov are published. Some of them contain geographical description of the Ukrainian lands. The textbook on the geography of Ukraine by A. Ivanivskyi is published in Ukrainian. Significant contribution to the methodological thought of this time was made by S. Rusova. who recognizes geography as an important educational discipline, pays attention to the necessity of studying physical and economic geography at school. Her textbook «Primary Geography» for the first time provides interesting material about Ukraine. Another important document for the development of school geographic education at the time of the national revolution of Ukraine at the beginning of the XX century became the «Project of Unified School in the Ukraine», which summed up the achievements of pedagogical thought and outlined the directions of school reform. The significant place in the «Project ...» is devoted to the science about nature, as they introduce children to the phenomena of life through zoology, botany, mineralogy, physics, chemistry, geography. We classify this document as the source of the study of the formation and development of school geographic education during the times of liberation struggles, which caused great deal of attention of the organizers of education to the study of geographical knowledge.